2019
DOI: 10.3168/jds.2018-15484
|View full text |Cite
|
Sign up to set email alerts
|

Quantification by simulation of the effect of herd management practices and cow fertility on the reproductive and economic performance of Holstein dairy herds

Abstract: The performance of dairy herds is affected mainly by factors related to cows' characteristics and herd management practices. However, these factors are interrelated, and as such, the estimation of their individual effect on the performance of dairy herds remains difficult. The aim of this study was to estimate the weight of these factors as well the interactions between them on the reproductive and economic performance of dairy farms. A stochastic dynamic model was used to simulate most physiological and manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
1
13
0
1
Order By: Relevance
“…Higher reproductive performance determines faster 21-d PR establishment and, therefore, higher production of calves, which is translated into a higher net return. Previous research consistently agreed that greater calf sales or greater value of offspring are a consequence of improved reproductive efficiency (Cabrera 2012;Giordano et al 2012;Kalantari and Cabrera 2012;Galvao et al 2013;Bekara and Bareille 2019). Our study compared different 21-d PR for all evaluated farms and showed similar results.…”
Section: Comparison Of Different Level Of 21-d Pr and Economic Outputsupporting
confidence: 80%
See 4 more Smart Citations
“…Higher reproductive performance determines faster 21-d PR establishment and, therefore, higher production of calves, which is translated into a higher net return. Previous research consistently agreed that greater calf sales or greater value of offspring are a consequence of improved reproductive efficiency (Cabrera 2012;Giordano et al 2012;Kalantari and Cabrera 2012;Galvao et al 2013;Bekara and Bareille 2019). Our study compared different 21-d PR for all evaluated farms and showed similar results.…”
Section: Comparison Of Different Level Of 21-d Pr and Economic Outputsupporting
confidence: 80%
“…Several authors have developed methodologies to estimate the financial cost of delayed pregnancy in dairy systems, based on computer simulation models (Groenendaal et al 2004;Meadows et al 2005;De Vries 2006;Kalantari and Cabrera 2015;Bekara and Bareille 2019). Although the use of those models made it possible to obtain quite realistic results, the real data from farms was not used in these studies, which could make it difficult to comprehend them by users.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations